1970
DOI: 10.1001/archneur.1970.00480300050006
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry of Adrenal Bodies in Parkinson's Disease

Abstract: AmsterdamI N 1912, Lewy1 described cytoplasmic hyaline inclusions in the substantia innominata and the dorsal vagal nucleus in paralysis agitans. Tr\l=e'\tiakoff2 described these inclusion bodies in the substantia nigra. In a previous paper3 I discussed the significance attached by various authors to these Lewy bodies, demonstrating additionally by a lipid-histochemical study that these Lewy bodies contain sphingomyelin. The next question concerned the relationship between the partial disintegration of such st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Although they are not considered neurons, chromaffin cells of the adrenal medulla were the first cells shown to secrete catecholamines (hence, the term adrenaline ). den Hartog Jager found that PD patients display large inclusion bodies in these cells, which he called “adrenal bodies.” LP was subsequently described as present in adrenal neurons . However, later work indicated that adrenal chromaffin cells themselves did not show LP, and the adrenal bodies described by den Jager were not immunoreactive for SYN .…”
Section: Vulnerable Neuronal Populations In Pdmentioning
confidence: 99%
“…Although they are not considered neurons, chromaffin cells of the adrenal medulla were the first cells shown to secrete catecholamines (hence, the term adrenaline ). den Hartog Jager found that PD patients display large inclusion bodies in these cells, which he called “adrenal bodies.” LP was subsequently described as present in adrenal neurons . However, later work indicated that adrenal chromaffin cells themselves did not show LP, and the adrenal bodies described by den Jager were not immunoreactive for SYN .…”
Section: Vulnerable Neuronal Populations In Pdmentioning
confidence: 99%
“…The adrenal gland is evolutionarily related to the sympathetic ganglia, and its capsula contains autonomic nerves and ganglia. There is evidence of involvement of the peripheral ANS in the adrenal gland in PD 89–91. One group reported adrenomedullary inclusions (adrenal bodies) in some patients, which they recognized to be Lewy‐body‐related (though they were also associated with other neurological diseases) 92.…”
Section: Adrenal Glandmentioning
confidence: 99%
“…It was already known that PAS-reactive adrenomedullary inclusions are mainly located on the medulla side of the corticomedullary border, and are unevenly distributed in the adrenal medulla. 7 Therefore, the number of adrenomedullary inclusions per unit area of the adrenal medulla was calculated for each autopsy patient as follows: (i) we counted the PAS-reactive adrenomedullary inclusions in the relevant adrenal section; (ii) we measured the sectional area of the adrenal medulla, which is immunoreactive to chromogranin A; and (iii) the number of adrenomedullary inclusions was divided by the value of the sectional area of the adrenal medulla to calculate the number of adrenomedullary inclusions per unit area. Then Wilcoxon's rank-sum testing, a nonparametric statistic method, was applied for a patient-control study of numbers of adrenomedullary inclusions per unit area.…”
Section: Calculation Technique and Statistics For Adrenomedullary Incmentioning
confidence: 99%
“…They have concluded that ‘hyaline globules’ are associated with chronic neural disorders. Furthermore, den Hartog Jager has observed ‘adrenal bodies’, which are spherical and eosinophilic cytoplasmic inclusion bodies, on the medulla side of the corticomedullary border in two patients with PD, whereas ‘adrenal bodies’ were absent in nine controls out of 10 7 7,8 and spectrochemically identified presence of sulfur, calcium and phosphorus 9 in both ‘adrenal bodies’ and Lewy bodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation